Fração e sua representação como medida de comprimento: uma experiência de ensino-aprendizagem no contexto de um laboratório de educação matemática - SANTOS, Nayra da Cunha Rossy (Universidade Federal do Pará, 2017)
The present study investigated the process of conceptual reconstruction fraction as a measure of length in the context of a Mathematics Laboratory Education (LEM) when the process is driven by a structured writing activity and mediated intervention of a teacher. To this end, the concepts of LEM were presented, choosing one as the design used for the survey. LEM offers possibilities that the teacher and students as an area of knowledge production, directing for Teaching Activities for which subsidized by Historic-Cultural Psychology, justifies the pedagogical activity of teachers and presents Guiding Teaching Activities were explored as an alternative to minimize some difficulties in teaching and learning, emphasizing conceptual learning. Structured with a class of 40 students in the 6th grade of elementary school in a public school in Belém, which was recorded on video and audio, for later microgenetic analysis of the interactions between teacher and students activity was applied. Taking into consideration the prior knowledge of students, work with the class during the year and structured activity, the results showed evidence of at least ten specific learning had an exponential effect on later learning. This means that the more previous connections are possible to be mobilized by the students in their interactions with the teacher, the more the subject is able to move forward in the consolidation of the object of study.